Conductive Hydrogel Conduits with Growth Factor Gradients for Peripheral Nerve Repair in Diabetics with Non‐Suture Tape. Issue 16 (21st June 2022) - Cai, Yuting; Huang, Qun; Wang, Penghui; Ye, Kaichuang; Zhao, Zhen; Chen, Haomin; Liu, Zhenjing; Liu, Hongwei; Wong, Hoilun; Tamtaji, Mohsen; Zhang, Kenan; Xu, Feng; et al.
Abstract: Diabetic patients suffer from peripheral nerve injury with slow and incomplete regeneration owing to hyperglycemia and microvascular complications. This study develops a graphene‐based nerve guidance conduit by incorporating natural double network hydrogel and a neurotrophic concentration gradient with non‐invasive treatment for diabetics. GelMA/silk fibroin double network hydrogel plays quadruple roles for rapid setting/curing, suitable mechanical supporting, good biocompatibility, and sustainable growth factor delivery. Meanwhile, graphene mesh can improve the toughness of conduit and enhance conductivity of conduit for regeneration. Here, novel silk tapes show quick and tough adhesion of wet tissue by dual mechanism to replace suture step. The in vivo results demonstrate that gradient concentration of netrin‐1 in conduit have better performance than uniform concentration caused by chemotaxis phenomenon for axon extension, remyelination, and angiogenesis. Altogether, GelMA/silk graphene conduit with gradient netrin‐1 and dry double‐sided adhesive tape can significantly promote repairing of peripheral nerve injury and inhibit the atrophy of muscles for diabetics. Abstract : Diabetic patients suffer from peripheral nerve injury (PNI) with slow regeneration owing to hyperglycemia and microvascular complications. To enable full recovery from PNI, this study develops a graphene‐based guidance conduit by incorporating natural double network (GelMA/silk fibroin) hydrogel and a neurotrophic concentration gradient (netrin‐1) with non‐invasive treatment (silk fibroin tapes) for diabetic mouse model.